The Business Process of Selling Ready Stock and Pre Order Items through E-Commerce System : an Indonesian SME Case Study - Retnaning Ayu Dyah Sawitri; Jaswadi; Andi Kusuma Indrawan (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to offer efficient business process modeling to overcome the problem in the sales quotation section of the sales cycle of pre-order by requesting products and the problem in the sales order section for sales cycle of ready-stock and pre-orders  products by requesting products. The method used was qualitative, with direct observation of the fashion business object of the Sakinah_id MSME. The study results showed that an e-commerce system was needed to facilitate electronic form features by request and separate sales order menus for ready and by request products. This form feature makes it easier for buyers to describe products according to requests and connect with the designer system. Based on the very short time gap from submitting the form, so that sales quotes can be followed up on promptly. The existence of an effective sales quotation provides a profitable domino effect in the next stage, namely that many prospective buyers agree and decide to place a sales order. Then the separation of the sales order menu for ready and pre-order products is needed because the handling of the two products is different, and pre-orders must start from the sales quotation stage, while ready products start from the sales order stage. This separation makes it easier and faster for employees to divide work through clear departmental boundaries for two products at the shipping stage, recording cash receipts, and scheduling special pre-order production.